Peran Konsep Diri dalam Mengurangi Konsekuensi Psikologis dari Cyberbullying - Khairatun Hisan; Nur Hamidah; Aysah Aurellia Rosspertiwi; Velda Murdiana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research investigates the psychological impact of cyberbullying on individuals' self-concept and analyzes the strategies and coping mechanisms used to reduce the negative consequences that arise. Using a qualitative approach, in-depth interviews were conducted with a number of participants who had experienced cyberbullying. Findings suggest variation in how individuals respond to these experiences, with some experiencing reduced self-esteem, while others develop adaptive strategies to cope with the psychological impact. Social support, developing mental resilience, self-reflection, managing social media, and seeking professional help were identified as key strategies. The results of this study provide in-depth insight into the complexity of the impact and individual responses to cyberbullying, and provide a foundation for the development of more effective interventions.